2007
DOI: 10.1016/j.virusres.2007.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular localization of the SARS coronavirus protein 9b: Evidence of active export from the nucleus

Abstract: Open reading frame 9b (ORF 9b) encodes a 98 amino acid group-specific protein of severe acute respiratory syndrome (SARS) coronavirus (CoV). It has no homology with known proteins and its function in SARS CoV replication has not been determined. The N-terminal part of the 9b protein was used to raise polyclonal antibodies in rabbits, and these antibodies could detect 9b protein in infected cells. We analyzed the sub-cellular localization of recombinant 9b protein using fluorescence microscopy of live transfect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
26
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 23 publications
(20 reference statements)
3
26
1
Order By: Relevance
“…5, mask), which indicates that the two proteins are less than about 200 nm apart, reinforcing the notion that proteins 6 and 9b may interact in vivo. The expression of protein 9b in SARS-CoV infected cells was observed partially localized both in the cytoplasm and in the nucleus, in agreement with the described subcellular localization of recombinant 9b protein in transfected cells (Moshynskyy et al, 2007;von Brunn et al, 2007) and in SARS-CoV infected cells at similar hpi (Sharma et al, 2011) (Fig. 5, merge).…”
supporting
confidence: 89%
“…5, mask), which indicates that the two proteins are less than about 200 nm apart, reinforcing the notion that proteins 6 and 9b may interact in vivo. The expression of protein 9b in SARS-CoV infected cells was observed partially localized both in the cytoplasm and in the nucleus, in agreement with the described subcellular localization of recombinant 9b protein in transfected cells (Moshynskyy et al, 2007;von Brunn et al, 2007) and in SARS-CoV infected cells at similar hpi (Sharma et al, 2011) (Fig. 5, merge).…”
supporting
confidence: 89%
“…Protein 9b contains no known NLS and enters the nucleus by passive diffusion (Sharma et al, 2011). However, amino-acid residues 46 to 54 (LRLGSQLSL) of p9b belong to a nuclear export signal (NES) motif LX 1-3 LX 2-4 LXL known to be transported by exportin 1 via an energy-dependent mechanism (Moshynskyy et al, 2007). Indeed, SARS-CoV p9b has been shown to physically interact with exportin 1 and moreover, mutation of the leucine-rich NES or inhibition of exportin 1 by leptomycin B have been shown to inhibit nuclear export of the 9b protein (Sharma et al, 2011;Moshynskyy et al, 2007).…”
Section: Sars-cov P8a P8b and P8abmentioning
confidence: 99%
“…However, amino-acid residues 46 to 54 (LRLGSQLSL) of p9b belong to a nuclear export signal (NES) motif LX 1-3 LX 2-4 LXL known to be transported by exportin 1 via an energy-dependent mechanism (Moshynskyy et al, 2007). Indeed, SARS-CoV p9b has been shown to physically interact with exportin 1 and moreover, mutation of the leucine-rich NES or inhibition of exportin 1 by leptomycin B have been shown to inhibit nuclear export of the 9b protein (Sharma et al, 2011;Moshynskyy et al, 2007). The nuclear export of p9b facilitates its degradation in the cytoplasm, whereas accumulation of p9b in the nucleus can induce caspase-dependent apoptosis (Sharma et al, 2011).…”
Section: Sars-cov P8a P8b and P8abmentioning
confidence: 99%
“…Although the protein initially accumulates in the nucleolus [64], it subsequently translocates to the outer membrane of mitochondria [63,65]. Nuclear export of other accessory proteins, namely SARS-CoV ORF9b, has also been previously reported [66] but how this spatio-temporal distribution impacts on ORF3b behavior and function is still unclear [67]. In fact, one study has reported that ORF3b is localized primarily in the nucleus with no evidence of mitochondrial localization [68].…”
Section: Sars Accessory Proteinsmentioning
confidence: 99%
“…Both anti-9b antibody and ORF9b antigen have been detected in clinical samples from SARS patients [37,59], with the latter also detected in virus infected cells [37]. Analysis, using fluorescence microscopy of live transfected cells and indirect immunofluorescence of transfected fixed cells, shows that ORF9b is exported outside of the cell nucleus and localizes to the endoplasmic reticulum [66,122]; the authors suggest that the 46-LRLGSQLSL-54 amino acid sequence motif of ORF9b functions as a nuclear export signal (NES) [66]. More recently, it was confirmed that ORF9b interacts with the cellular protein Crm1 and gets exported out of the nucleus using an active NES; this nucleocytoplasmic export of ORF9b is linked to apoptosis [123].…”
Section: Sars Accessory Proteinsmentioning
confidence: 99%